Return to competition in a chronic low back pain runner: beyond a therapeutic exercise approach, a case report - Sergio Veneziani; Christian Doria; Luca Falciati; Claudio Carlo Castelli; Giorgio Fanò Illic (PAGEPress Publications, 2014)
Chronic low back pain (CLBP) is a disabling condition affecting both quality of life and performance in athletes. Several approaches have been proposed in the field of physiotherapy, manual therapy, physical exercise and counseling. None apparently is outdoing the other with the exception of trunk stability exercises in specific conditions. The present paper describes a clinical success in managing a CLBP runner affected by MRI documented disk herniation via dietary change. Dietary changes allowed our patient that had failed with previous standard therapeutic approaches, to regain an optimal pain-free condition. We advance the hypothesis that a visceral-autonomic concomitant or primary disturbance possibly generating mild gastrointestinal discomfort in CLBP patients should be ruled out as a possible cause of pain and disability at the somato-motor level.